Effects of stratification, organic matter remineralization and bathymetry on summertime oxygen distribution in the Bohai Sea, China. (15th February 2017) - Zhao, Hua-De; Kao, Shuh-Ji; Zhai, Wei-Dong; Zang, Kun-Peng; Zheng, Nan; Xu, Xue-Mei; Huo, Cheng; Wang, Ju-Ying
Abstract: The Bohai Sea, a semi-enclosed shallow coastal sea with increasing nutrient loads, is susceptible to seasonal oxygen deficiency in its bottom waters, similar to many other areas of the worlds' coastal oceans. We examined the dissolved oxygen (DO) distribution in the Bohai during August 2014. Two oxygen-deficient zones (DO<92 μmol O2  kg −1 ) with a minimum DO of ~80 μmol O2  kg −1 were documented. The area and volume of bottom oxygen-deficient water were ~756 km 2 and 7820×10 6 m 3, with a mean thickness of ~10 m. Thus, the Bohai is second to the Changjiang estuary in its oxygen-deficient zone size among China's coastal waters. We classified three hydrographic areas that dictated the distribution of DO: 1) the shallow well-mixed zone; 2) the laterally-open stratified zone; and 3) the isolated stratified zone. Vertical mixing dominated the shallow well-mixed zone leading to homogeneous DO in the water column. The laterally-open stratified zone was influenced by high DO and low temperature inflow through the northern Bohai Strait. The isolated stratified zones, i.e., the low DO areas, were found in depressed regions. The stoichiometric relationship between DO consumption and the corresponding enrichment of dissolved inorganic carbon suggested that the aerobic respiration of organic matter contributed to the oxygen-depletion in the isolated stratified zone. Overall, the bottom DO distribution in the Bohai system was controlled largely by lateral DO exchange modified by bathymetric features, while superimposed on that was the build-up of stratification caused by summer heating and the remineralization of organics sourced from spring phytoplankton bloom. Graphical abstract: Highlights: Area and volume of oxygen-deficient water in the Bohai Sea are estimated. Three subzones are categorized based on DO distribution and controlling mechanisms. DO is mainly controlled by stratification, organics remineralization and bathymetry